Unveiling the therapeutic potential of exogenous β-hydroxybutyrate for chronic colitis in rats: novel insights on autophagy, apoptosis, and pyroptosis - Abdelhady, Rasha; Saber, Sameh; Ahmed Abdel-Reheim, Mustafa; Mohammad S. Alamri, Mohannad; Alfaifi, Jaber; I. E. Adam, Masoud; A. Saleh, Lobna; I. Farag, Azza; A. Elmorsy, Elsayed; S. El-Wakeel, Hend; S. Doghish, Ahmed; E. Shaker, Mohamed; et al. (Frontiers in Pharmacology, 2023)
Ulcerative colitis (UC) is a chronic relapsing inflammatory disease of the colorectal area that demonstrates a dramatically increasing incidence worldwide. This study provides novel insights into the capacity of the exogenous β-hydroxybutyrate and ketogenic diet (KD) consumption to alleviate dextran sodium sulfate (DSS)-induced UC in rats. Remarkably, both interventions attenuated disease activity and colon weight-to-length ratio, and improved macro and microstructures of the damaged colon. Importantly, both β-hydroxybutyrate and KD curbed the DSS-induced aberrant NLRP3 inflammasome activation as observed in mRNA and protein expression analysis. Additionally, inhibition of the NLRP3/NGSDMD-mediated pyroptosis was detected in response to both regimens. In parallel, these modalities attenuated caspase-1 and its associated consequences of IL-1β and IL-18 overproduction. They also mitigated apoptosis as indicated by the inactivation of caspase-3. The anti-inflammatory effects of BHB and KD were confirmed by the reported decline in the levels of inflammatory markers including MPO, NFκB, IL-6, and TNF-α. Moreover, these interventions exhibited antioxidative properties by reducing ROS production and improving antioxidative enzymes. Their effectiveness in mitigating UC was also evident in the renovation of normal intestinal epithelial barrier function, as shown by correcting the discrepancies in the levels of tight junction proteins ZO-1, OCLN, and CLDN5. Furthermore, their effects on the intestinal microbiota homeostasis were investigated. In terms of autophagy, exogenous β-hydroxybutyrate upregulated BECN-1 and downregulated p62, which may account for its superiority over KD in attenuating colonic damage. In conclusion, this study provides experimental evidence supporting the potential therapeutic use of β-hydroxybutyrate or β-hydroxybutyrate-boosting regimens in UC.